Efektivitas Model Pembelajaran Self Directed Learning Terhadap Kemampuan Menulis Cerita Pendek Bagi Siswa Kelas X MA Ainul Hasan Maron Probolinggo - Latifah, Lutfiatul; Rusly, Fathullah; Susetya, Hemas Haryas Harja (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The aim of this research is to find out whether the self-directed learning model has a significant impact in improving the writing skills of MA Ainul Hasan Maron Probolinggo students. This research uses a quantitative approach with descriptive research type. Quantitative research is an empirical research approach to collecting, analyzing, and presenting data numerically rather than in narrative form. Therefore, to collect data, identify variables and measure them numerically so that analysis can be carried out in accordance with applicable statistical methods. The aim of quantitative research is none other than drawing conclusions or generalizing appropriate predictive theories. This research took the population of MA Ainul Hasan, while the sample chosen was class X students of MA Ainul Hasan. The results of this research show that the self-directed learning model is quite significant in improving the short story writing ability of class X MA Ainul Hasan Maron Probolinggo students.